1999
DOI: 10.1126/science.286.5438.309
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Negative Regulator c-Cbl as a RING-Type, E2-Dependent Ubiquitin-Protein Ligase

Abstract: Ubiquitination of receptor protein-tyrosine kinases (RPTKs) terminates signaling by marking active receptors for degradation. c-Cbl, an adapter protein for RPTKs, positively regulates RPTK ubiquitination in a manner dependent on its variant SRC homology 2 (SH2) and RING finger domains. Ubiquitin-protein ligases (or E3s) are the components of ubiquitination pathways that recognize target substrates and promote their ligation to ubiquitin. The c-Cbl protein acted as an E3 that can recognize tyrosine-phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
792
2
7

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 951 publications
(815 citation statements)
references
References 27 publications
14
792
2
7
Order By: Relevance
“…Ubiquitylation of EGFR and subsequent degradation controls the intensity of downstream signals after receptor activation. c-Cbl, a ubiquitin E3 ligase, is recruited to EGFR upon ligand stimulation, and then initiates the ubiquitylation of the activated receptor (Joazeiro et al, 1999;Levkowitz et al, 1999). The ubiquitylated EGFR is internalized into early endosomes, from where it is either recycled to plasma membrane, or delivered to multivesicular bodies and late endosomes for degradation (Waterman and Yarden, 2001;Ravid et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitylation of EGFR and subsequent degradation controls the intensity of downstream signals after receptor activation. c-Cbl, a ubiquitin E3 ligase, is recruited to EGFR upon ligand stimulation, and then initiates the ubiquitylation of the activated receptor (Joazeiro et al, 1999;Levkowitz et al, 1999). The ubiquitylated EGFR is internalized into early endosomes, from where it is either recycled to plasma membrane, or delivered to multivesicular bodies and late endosomes for degradation (Waterman and Yarden, 2001;Ravid et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether IAP protein Livin, like other RING finger proteins, can regulate itself through auto-ubiquitination, 11,23,24 we compared the endogenous Livin in the presence or absence of proteasome inhibitor MG132 or ALLN. We found that Livin is regulated by self-ubiquitination, and as a result, Livin undergoes proteasome-mediated degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The ERK pathway affects EGFR trafficking by threonine phosphorylation of EGFR Consequent to EGF stimulation, activated EGFR is rapidly ubiquitinated by c-Cbl, an SH2 domain-containing ubiquitin ligase that itself becomes phosphorylated and binds to EGFR, which promotes postinternalization of EGFR and sorting to endosomes and lysosomes for degradation (Levkowitz et al, 1998;Joazeiro et al, 1999;Waterman et al, 1999). In DU145 cells, EGF stimulation led to EGFR ubiquitination (Figure 3a, upper panel, lane 2), which was enhanced by PD98059 (lane 4 vs 2), but not by LY294002 (lane 6 vs 2).…”
Section: Inhibition Of the Erk Pathway Enhances Egf-induced Egfr Actimentioning
confidence: 99%